Optimizing last-mile food delivery - Soh, Cecilia Hui Chin (Nanyang Technological University, 2024)
This study addresses the growing challenges in last-mile delivery logistics, particularly after the surge in demand for food delivery services post-COVID-19. Issues like increased traffic congestion, higher operational costs, and greater environmental impacts from frequent delivery trips highlight the need for optimized delivery strategies.